Pergeseran Paradigma Moral dalam KUHP Nasional: Analisis Filosofis dan Implikasi Yuridis - Debi Rosalina; Parningotan Malau (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
The shift in moral paradigms within the Indonesian National Criminal Code (KUHP) represents a fundamental transformation in the orientation of criminal law reform. Departing from the colonial legal-positivistic framework, the 2023 KUHP increasingly incorporates public morality and communitarian values as bases for criminalization. Through a philosophical and juridical normative analysis, this study demonstrates that the most critical implication of this shift is the erosion of the principle of legality (lex certa), particularly in morality-based offenses whose vague formulations grant broad interpretative discretion to law enforcement authorities. The findings reveal that several decency-related provisions extend state intervention into the private sphere without a clear demonstration of concrete harm, thereby increasing the risk of overcriminalization and inconsistent legal enforcement. While the new KUHP seeks to harmonize local moral values with constitutional principles and human rights, this study argues that the absence of precise normative boundaries weakens legal certainty and threatens the protection of individual rights. The article emphasizes the need for a balanced integration of public morality, legal certainty, and human rights in the ongoing implementation of the National Criminal Code.